Heart failure in patients with kidney disease. Issue 23 (17th July 2017) - Tuegel, Courtney; Bansal, Nisha
Abstract : Heart failure (HF) is a leading cause of morbidity and mortality in patients with chronic kidney disease (CKD), and the population of CKD patients with concurrent HF continues to grow. The accurate diagnosis of HF is challenging in patients with CKD in part due to a lack of validated imaging and biomarkers specifically in this population. The pathophysiology between the heart and the kidneys is complex and bidirectional. Patients with CKD have greater prevalence of traditional HF risk factors as well as unique kidney-specific risk factors including malnutrition, acid-base alterations, uraemic toxins, bone mineral changes, anemia and myocardial stunning. These risk factors also contribute to the decline of kidney function seen in patients with subclinical and clinical HF. More targeted HF therapies may improve outcomes in patients with kidney disease as current HF therapies are underutilised in this population. Further work is also needed to develop novel HF therapies for the CKD population.